Development of Encyclopedia of Art, Culture, and Tourism in Palembang - Syarifuddin Syarifuddin; Alian Alian; Sani Safitri (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research on art, culture, and tourism tries to provide the latest information about the cultural treasures in Palembang. It uses ADDIE Model to research and develop the prototypes. The product has gone through an expert revision stage carried out by 3 experts with attached comments giving the result that this encyclopedia product is deemed feasible. In the next stage, one-to-one learner test stage, it receives comments and suggestions from three students as a reference for the revisions so that product shortages are greatly reduced. In the small group test stage, very constructive comments and suggestions were received to make the product even better before it is then moved to the test stage in which it gets a result of tabulation score of 4.10, which means the prototype is suitable for finalization as a finished product. The results of this study conclude that the encyclopedia produced is suitable to be used as a handbook either for the government, academics (universities, schools, and related educational institutions), tourists (at home and abroad), as well as the people of Palembang themselves.